2022
DOI: 10.3389/fphar.2022.787113
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Identifying Potentially Inappropriate Prescriptions for Children and Their Applicability in Clinical Practices: A Systematic Review

Abstract: Background: Drug use safety in children is a global public health problem. The potentially inappropriate prescription screening tools are expected to reduce adverse drug reactions and promote rational drug use.Objectives: To systematically evaluate children’s potentially inappropriate prescription screening tools and validation studies on these tools.Methods: We systematically searched six databases PubMed, Embase, Cochrane Library, CNKI, VIP and Wanfang Data. Two reviewers independently selected articles by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…A manual search of reference lists did not yield any additional relevant publications. Ultimately, 23 records, including 15 systematic reviews 12,[14][15][16][17][18][19][34][35][36][37][38][39][40][41] and eight guidelines, [42][43][44][45][46][47][48][49] were included in this review (Figure 1). The detailed characteristics of these systematic reviews and guidelines can be found in Tables 1 and 2, respectively.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…A manual search of reference lists did not yield any additional relevant publications. Ultimately, 23 records, including 15 systematic reviews 12,[14][15][16][17][18][19][34][35][36][37][38][39][40][41] and eight guidelines, [42][43][44][45][46][47][48][49] were included in this review (Figure 1). The detailed characteristics of these systematic reviews and guidelines can be found in Tables 1 and 2, respectively.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…Unfortunately, the development and research of PIP detection tools for children are insufficient and limited. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Prescribing appropriate medication prescription is the basis for optimising children’s medical and health services and reducing ADRs. Unfortunately, the development and research of PIP detection tools for children are insufficient and limited 19…”
Section: Introductionmentioning
confidence: 99%
“…In the pediatric population, the incidence of ADRs in inpatients is 9.53% and in outpatients is 1.46%; and the incidence of ADRs leading to hospital admission in children is 2.09% ( Impicciatore et al, 2001 ). Unlike the elderly, the development of explicit PIP criteria for children is in its infancy, and there are only five PIP criteria for children ( Prot-Labarthe et al, 2011 ; Barry et al, 2016 ; Corrick et al, 2019 ; Meyers et al, 2020 ; Sadozai et al, 2020 ; Li et al, 2022 ). Experts in France were the first to develop the PIP criteria for children.…”
Section: Introductionmentioning
confidence: 99%
“…They released the POPI criteria (Pediatrics: Omission of Prescriptions and Inappropriate Prescriptions) in 2011 ( Prot-Labarthe et al, 2011 ), then the United Kingdom ( Barry et al, 2016 ; Corrick et al, 2019 ) and the US ( Meyers et al, 2020 ) successively released their PIP criteria for children. We previously conducted a comprehensive systematic review on existing tools for identifying PIPs in children and their applicability in clinical practices ( Li et al, 2022 ) and regrettably found that China has not yet developed a tool for detecting PIPs in children based on its actual clinical practice.…”
Section: Introductionmentioning
confidence: 99%